The impact of medical ball training in muscle strength and shoulder joint rehabilitation for athletes who throw (Journal of Humanities and Social Sciences Research, 2022)
The purpose of this study was to create and test a series of exercises using a medical ball to increase muscular strength and repair the shoulder joint for young athletes. The throwing forces (spear, hammer, shot put, discus) for the season 2022-2023, whose number is (8) players, and then applied the exercises set along the course period, and obtaining data that was treated statistically and obtaining information on which conclusions were based, the most important of which was for specific exercises with the ball. The medical field plays an important role in growing muscular strength and thereby repairing the shoulder joint for throwing athletes, as well as in strengthening and improving the motor program. It is appropriate for training this age group, as well as saving time for the coach and player in increasing the muscle strength of athletics competitors.